Promoting Social Welfare: Maqasid Sharia Compliance of Indonesian Hajj Financial Manegement Agency’s Maslahat Program - Hidayat, Rahmat (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2024)
BPKH (Hajj Financial Management Agency) was established based on the mandate of Law Number 34 of 2014 concerning Hajj Financial Management. The purpose of managing hajj finances is to improve the quality of hajj service management, the rationality and efficiency of Hajj Pilgrimage Costs (BPIH), and the welfare of Muslims. To achieve the three goals above, BPKH implements welfare programs in the form of corporate social responsibility (CSR) or